Acceptance towards Monkeypox Vaccination: A Systematic Review and Meta-Analysis - Ulloque-Badaracco, Juan R. (2022)
Vaccination it is considered a vital strategy in order to mitigate monkeypox by protecting from severe disease and helping in reduction of hospitalisations. In this sense, this study aims to estimate the global prevalence of vaccination acceptance against monkeypox. We conducted a systematic review with a comprehensive search strategy for the following databases: PubMed, Scopus and Web of Science. A random-effect model meta-analysis was carried out using observational studies assessing the intention of vaccines against monkeypox from multiple continents. The quality assessment was developed using the Newcastle-Ottawa Scale adapted for cross-sectional studies. In addition, a subgroup analysis by study location and population and a sensitivity analysis was developed.Eleven cross-sectional studies were included. A total of 8045 participants were included. The pooled prevalence of monkeypox vaccination acceptance in all participants was 56.0% (95%CI: 42.0–70.0%). In the subgroup analysis of monkeypox vaccine acceptance according to continents, the prevalence of vaccine acceptance was 50.0% (95%CI: 24.0–76.0%) in Asian countries and 70.0% (95%CI: 55.0–84.0%) in European countries. The prevalence of vaccine acceptance was 43.0% (95%CI: 35.0–50.0%) in the general population, 63.0% (95%CI: 42.0–70.0%) in healthcare workers, and 84.0% (95%CI: 83.0–86.0%) in the LGBTI community. Despite the high prevalence of monkeypox vaccination acceptance in the LGBTI community found in our study, vaccination acceptance from healthcare workers and the general population are lower. Governments could use these results for planning, developing or promoting vaccination strategies and public health policies focused on these populations.